2021
DOI: 10.5888/pcd18.210091
|View full text |Cite
|
Sign up to set email alerts
|

Extent of Inclusion of “Rural” in Comprehensive Cancer Control Plans in the United States

Abstract: What is already known on this topic? States, territories, and tribal organizations are required to develop comprehensive cancer control plans that describe the cancer burden and disparities in their jurisdiction and provide goals, objectives, and strategies to address cancer.What is added by this report? About two-thirds of states, territories, and tribal organizations considered "rural" in their plans; only about one-third of plans included a rural-specific strategy.What are the implications for public health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…In 2019, the CDC National Comprehensive Cancer Control Program began asking state, territorial, and tribal health departments to consider rural populations in their local cancer control plans. 20 Unfortunately, as of early 2023, less than one-third of all state, territorial, or tribal comprehensive cancer control plans incorporate a dedicated strategy for addressing the needs of rural populations. This represents a significant failure in policy development and a loss of opportunity.…”
Section: Rural Area Of Residence and Policymentioning
confidence: 99%
“…In 2019, the CDC National Comprehensive Cancer Control Program began asking state, territorial, and tribal health departments to consider rural populations in their local cancer control plans. 20 Unfortunately, as of early 2023, less than one-third of all state, territorial, or tribal comprehensive cancer control plans incorporate a dedicated strategy for addressing the needs of rural populations. This represents a significant failure in policy development and a loss of opportunity.…”
Section: Rural Area Of Residence and Policymentioning
confidence: 99%
“…One recommendation was for the CDC to require state jurisdictions to assess rural cancer mortality burden and develop goals, objectives, and strategies to address disparities through their CCC plans [ 13 ]. A recent assessment of state CCC plans found that over two-thirds included the term “rural,” but only about a third included rural-specific goals, objectives, or strategies [ 14 ]. Engaging rural partners in the planning process may facilitate the inclusion of data on rural cancer burden and corresponding goals and objectives to reduce disparities, in accordance with recommendations from NACRHHS and the CDC’s Self-Assessment Tool [ 2 , 13 ].…”
Section: Introductionmentioning
confidence: 99%